2020
DOI: 10.1002/chem.202000495
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Affinity of an O‐Antigen Polysaccharide Binding Site in Shigella flexneri Bacteriophage Sf6 Tailspike Protein

Abstract: Broad and unspecific use of antibiotics accelerates spread of resistances. Sensitive and robust pathogen detection is thus important for a more targeted application. Bacteriophages contain a large repertoire of pathogen‐binding proteins. These tailspike proteins (TSP) often bind surface glycans and represent a promising design platform for specific pathogen sensors. We analysed bacteriophage Sf6 TSP that recognizes the O‐polysaccharide of dysentery‐causing Shigella flexneri to develop variants with increased s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…A recent MD simulations study reported that two Sf6TSP E366A D399A variants (V204C and S246C) that are in close proximity to the Oag binding site, had a slight increase in binding affinity to serotype Y LPS Oag (Kunstmann et al . 2020 ). This indicated that Sf6TSP can be engineered to increase its binding affinity to LPS Oag.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent MD simulations study reported that two Sf6TSP E366A D399A variants (V204C and S246C) that are in close proximity to the Oag binding site, had a slight increase in binding affinity to serotype Y LPS Oag (Kunstmann et al . 2020 ). This indicated that Sf6TSP can be engineered to increase its binding affinity to LPS Oag.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a trimeric Sf6TSP contains three independent elongated glycan binding sites for LPS Oag fragments (Kunstmann et al . 2020 ). Sf6TSP has been shown to interact with LPS Oag of serotype 2a weakly (Kunstmann et al .…”
Section: Introductionmentioning
confidence: 99%
“…Glucosylated 2a and 5a O-antigens have previously been shown to assume a helical rather than a linear shape in solution or in a complex with antibodies ( 40 , 41 ). Previous work using molecular dynamics demonstrated that mutations near the O-antigen binding site of the Sf6 tailspike can dramatically affect the flexibility of the site ( 42 ). As part of their study, Kunstmann et al ( 42 ) modeled a T443C substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using molecular dynamics demonstrated that mutations near the O-antigen binding site of the Sf6 tailspike can dramatically affect the flexibility of the site ( 42 ). As part of their study, Kunstmann et al ( 42 ) modeled a T443C substitution. While we isolated T443P here, the effect of increasing flexibility may be similar.…”
Section: Discussionmentioning
confidence: 99%
“…This extension of the methodological repertoire using effective proton−proton distances within a bound octasaccharide, which contains rhamnosyl residues, in complex with the Shigella f lexneri bacteriophage Sf6 tailspike protein together with two-dimensional ϕ,ψ distance-plots from MD simulations made it possible to define the bound conformation of the octasaccharide in the complex, in excellent agreement with the crystal structure of the complex. 79 Subsequent to elucidation of the conformation of a bound ligand by tr-NOESY NMR experiments the binding epitope of the ligand recognized by a protein can be investigated by saturation transfer difference (STD) NMR experiments. 80 In the technique, proton resonances of a protein, different from those of the ligand, are saturated and in transiently formed complexes this saturation affects the bound ligand whereby its proton peak intensities are attenuated in relation to proximity of the ligand to the protein.…”
Section: ■ Interactions (Recognition)mentioning
confidence: 99%